INTERCULTURAL COMMUNICATION DYNAMICS OF INDONESIAN IMMIGRANT WORKERS IN SAUDI ARABIA - Ryan Ichiro Martohasian; Nicholas; Ayu Wulandari (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2025)
The dynamics of intercultural communication experienced by Indonesian immigrant workers in Saudi Arabia is an issue in this study. With the cultural background that Indonesian citizens have as immigrant workers, there will certainly be complex dynamics of intercultural communication processes in everyday life, especially in the process of the work environment. This study aims to identify the factors that are crucial in the success of cross-cultural adaptation of Indonesian citizens in Saudi Arabia and also to analyze the personal experiences of Indonesian immigrants in the dynamic process of social interaction and cross-cultural adaptation in the work environment based on differences in language, values, norms and local habits. Using qualitative research methods and phenomenological traditions to determine the criteria for interviewees, namely people who do work in Saudi Arabia, which focuses on in-depth interviews with Indonesian immigrant workers to explore intercultural communication processes such as communication habits, cultural adaptation, the overall impact of intercultural communication dynamics in the work environment for Indonesian immigrant workers in Saudi Arabia.